CONSTRUCTION OF MATHEMATICAL MODELS WHEN SOLVING APPLIED PROBLEMS OF ECONOMIC CONTENT - Hrytsik, Tetyana (Physical and Mathematical Education, 2025)
Formulation of the problem. The article aims to systematize and generalize the main types of mathematical models used in solving applied economic problems within the higher mathematics course, as well as to determine the pedagogical conditions that foster the development of mathematical modeling skills among future economists.Materials and methods. The research employed a combination of theoretical and empirical methods, including an analysis of scientific and methodological literature on mathematical modeling, the synthesis and comparison of national and international studies, the systematization of typical economic–mathematical models, and pedagogical observations.Results.  The study substantiates the role of mathematical modelling as a core method in forming the professional competence of future economists. The main types of mathematical models used in economic problem-solving —matrix, vector, linear, integral, differential, and derivative-based models — were systematized. A generalized structural scheme of a mathematical model of an applied problem is proposed, integrating the stages of formalization, analysis, and interpretation, and reflecting the relationship between theoretical and quantitative components. It was found that the implementation of this sequence contributes to the development of research-oriented thinking and analytical skills of learners.Conclusion. The study reveals a contradiction between the growing need for economists capable of modelling and analyzing economic processes and the insufficient level of students’ mathematical training. It is proven that the systematic use of applied economic problems in the higher mathematics course promotes the formation of professional competences and the development of economic thinking. Further research should focus on the design of methodological tools and digital resources for teaching mathematical modeling, as well as on integrating modeling techniques into interdisciplinary economics-related courses.
Keywords: mathematical modeling; mathematical model; applied problem; higher mathematics; economic content; applied orientation